EFEKTIVITAS MODEL PROJECT BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA SMK NEGERI 1 PADANG - Yumu Rora Yahya; Arwizet K; Waskito Waskito; Eko Indrawan (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2026)
ABSTRACT Vocational education plays a crucial role in preparing graduates with competencies aligned with industrial demands. However, students' learning outcomes on lathe cutting parameter materials remain suboptimal due to teacher-centered instruction and the limited use of technology-based learning media. This study aimed to analyze the effectiveness of Project-Based Learning (PjBL) assisted by instructional videos on students' learning outcomes and to compare its effectiveness with conventional instruction. A quantitative approach employing a quasi-experimental method with a nonequivalent control group design was used. The participants consisted of 50 eleventh-grade machining engineering students at SMK Negeri 1 Padang, divided into an experimental class and a control class. Data were collected using a multiple-choice achievement test and analyzed through the Shapiro–Wilk normality test, Levene's homogeneity test, Independent Samples t-test, and N-Gain analysis. The results revealed a significant difference in learning outcomes between the two groups (p = 0.000), with the experimental class achieving a higher posttest mean score than the control class. Furthermore, the experimental class attained a high N-Gain score (0.701), while the control class achieved a moderate N-Gain score (0.419). These findings indicate that PjBL assisted by instructional videos is an effective instructional approach for improving students' learning outcomes on lathe cutting parameter materials. ABSTRAK Peningkatan kompetensi siswa pada pendidikan vokasi memerlukan pembelajaran yang mampu menghubungkan pemahaman konseptual dengan penerapan praktik. Namun, hasil belajar siswa pada materi parameter pemotongan mesin bubut masih belum optimal karena pembelajaran cenderung berpusat pada guru dan pemanfaatan media pembelajaran berbasis teknologi masih terbatas. Penelitian ini bertujuan menganalisis efektivitas penerapan Project Based Learning (PjBL) berbantuan video pembelajaran terhadap hasil belajar siswa serta membandingkannya dengan pembelajaran konvensional. Penelitian menggunakan pendekatan kuantitatif dengan metode quasi experiment dan desain nonequivalent control group design. Subjek penelitian berjumlah 50 siswa kelas XI Teknik Pemesinan di SMK Negeri 1 Padang yang terbagi menjadi kelas eksperimen dan kelas kontrol. Data dikumpulkan melalui tes hasil belajar, kemudian dianalisis menggunakan uji Shapiro–Wilk, uji Levene, Independent Sample t-test, dan N-Gain. Hasil penelitian menunjukkan terdapat perbedaan hasil belajar yang signifikan antara kedua kelas (Sig. = 0,000), dengan rata-rata posttest kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Nilai N-Gain kelas eksperimen berada pada kategori tinggi (0,701), sedangkan kelas kontrol berada pada kategori sedang (0,419). Temuan ini menunjukkan bahwa penerapan PjBL berbantuan video pembelajaran efektif meningkatkan hasil belajar siswa pada materi parameter pemotongan mesin bubut.